PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Kantor PT. Perkebunan Nusantara X (Persero) Pabrik Gula Lestari Nganjuk) - Musyaya, Antonius Adek; Sudiro, Achmad (Jurnal Ilmiah Mahasiswa FEB, 2013)
The work environment is circumstances of the surrounding workplace in physical and non-physical manner that can give enjoyable, secure, reassuring, and feel work at home impressions. The working environment is very important because it is closely related to the level of the employee performance, if the working environment better, it could give a positive influence on employeeâ€™ performance, and vice versa. This study uses the "explanatory researchâ€ approaching, that explain the causal relationship between the variables through hypothesis testing. The location of this research is the data collection office employees of PT. Perkebunan Nusantara X (Persero) Pabrik Gula Lestari, located on PG Lestari St., Ngrombot Village, Patianrowo sub-district, Nganjuk Regency. Based on the source, the data of this study consisted of primary data and secondary data. In collecting the data, the technique was used is: the spread of documentation and questionnaires with the respondents 34 employees. Data analysis techniques in this studyÂ  is multiple regressions that using SPSS 16.0. Based on the test results of multiple regression analysis it is known that the physical work environment and the non-physical to explain the employeesâ€™ performance is 26.9% while the rest is explained by other factors that unverified. Simultaneous hypothesis test to prove there is a significant effect on the physical environment and the non-physical work on employee performance. Partial hypothesis test to prove the physical work environment there is a significant influence on the performance of the employee while the non-physical work environment to prove there isÂ  a significant influence on the employee performance. The independent variables were the dominant influence on employeesâ€™ performance evidenced in the standardized beta coefficients table with the highest value of non-physical work environment in the amount of 0.497. KeywordÂ  :Â  Physical Work Environment, Non-PhysicalÂ  WorkÂ  Environment,Â  Employeesâ€™ Performance.